Effectiveness of Acceptance and Commitment Therapy on the Psychological Well-Being of Couples Referring to the Dispute Resolution Council - Karimzadeh, Kheirollah; Sodani, Mansour; Safarzadeh, Sahar; Koraei, Amin (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The objective of this study was to evaluate the effectiveness of Acceptance and Commitment Therapy (ACT) on the psychological well-being of couples referring to the Dispute Resolution Council in Omidiyeh County. Methods: This study employed a quasi-experimental design with a pre-test, post-test, and control group, along with a 45-day follow-up period. The statistical population consisted of couples who referred to the Dispute Resolution Council in Omidiyeh County in 2021. In the initial phase, a purposive sampling method was used to select 30 participants. These individuals were chosen from among those who had been engaged or married for four or five years, expressed a desire for separation, and had sought assistance from the Dispute Resolution Council. They were randomly assigned to either the experimental group or the control group. The experimental group underwent eight sessions of Acceptance and Commitment Therapy, while the control group received no intervention and remained on a waiting list. Findings: The mean age in the ACT group was 33.31 ± 5 years, in the solution-focused approach group was 32.50 ± 3.72 years, and in the control group was 33.68 ± 5.04 years. The results of the mixed-design analysis of variance indicated that the intervention had a statistically significant effect on the dimensions of psychological well-being in the post-test and follow-up stages compared to the control group (p < .05). Furthermore, the results of the Bonferroni post hoc test demonstrated that Acceptance and Commitment Therapy was more effective in improving conflict resolution styles (p < .05). Conclusion: Acceptance and Commitment Therapy can be considered an effective approach for reducing problems arising from marital conflicts among individuals referring to the Dispute Resolution Council.